Student mobility from new to old member states in the European Union - changing patterns after 1st of May 2004? - Nina Wolfeil (University of Warsaw, Centre of Migration Research (CMR), 2009)
Since Poland's accession to the European Union in 2004 traditional target countries of Polish labour migration have lost some of their importance in favour of emerging destinations such as the UK and Ireland. The paper uses this phenomenon as a starting point to analyse whether there are parallels between these labour mobility patterns and recent flows of student mobility from CEE. By means of a literature review it will be shown that student mobility may be understood as a subset of highly skilled migration and as a precursor of permanent migration. The presentation of recent data on the inflow of students from CEE to eight countries (Austria, Germany, Finland, France, United Kingdom, Ireland, the Netherlands, Sweden) of the EU-15 and on the outflow of students from the EU-8+2 reveals that traditional target countries (e.g. DE) have lost some of their attractiveness, while numbers of CEE-students in emerging targets (UK, IE) have been rising steeply since 2004. However, liberal labour market legislation with regard to CEE-graduates in the UK and Ireland is only one possible explaining factor for this. Amongst the complex bundle of determining factors an important role is played by tuition fee policies in the target countries (pull-factors) as well as demographic changes and entrance to tertiary education in the sending countries (push-factors).
Keywords: 330; Internationale Migration; Auswanderung; Studierende; Arbeitsmigranten; EU-Mitgliedschaft; EU-Mitgliedschaft; EU-Staaten